High Efficiency Focusing and Vortex Generator Based on Polarization-Insensitive Gallium Nitride Metasurface - Zhitong Sun; Bijun Xu; Bairui Wu; Xiaogang Wang; Hao Ying (Nanomaterials, 2021)
In this paper, two polarization-insensitive Gallium Nitride (GaN) metasurfaces based on a dynamic phase for adjusting the wavefront are proposed. Specifically, we obtained the target phase to satisfy some design conditions by changing the structural parameters at the nanoscales. Under the irradiation of linearly polarized (LP) light and circularly polarized (CP) light, respectively, one of the metasurfaces can generate a focused beam with an efficiency of 84.7%, and the other can generate a vortex beam with a maximum efficiency of 76.6%. Our designed metasurfaces will have important applications in optical communication, holographic projection, and particle capture.